A New Perspective of COVID-19 Infection: An Epigenetics Point of View - Ozturkler, Ziya; Kalkan, Rasime (Global Medical Genetics, 2021)
Coronavirus disease 2019 (COVID-2019) started in Wuhan, China, in December 2019. Angiotensin-converting enzyme 2 (ACE2) receptor was one of the most important genes related to the entrance of the virus to the host. Until now, several variations have been identified in ACE2 and related transmembrane protease serine 2. Epigenetic modifications not only play an important role during the maintenance of genome and cellular homoeostasis but also for the etiopathophysiology of the virus infection. Studies showed methylation of ACE2 was changed to depend on host and age of the host during the viral infection.In this study, we provided an epigenetics point of view to the coronavirus infection. We highlight the importance of epigenetic modifications during viral replication and infection and their interaction with COVID-19 susceptibility and host viral response.
Keywords: COVID-19; epigenetics; methylation